Teachers’ Perceptions of Multiple Trade Unions in Promoting Professional Development among Teachers - Tinus Range Elias; Freddie Iramba (Journal La Edusci, 2022)
The purpose of this study was to examine teachers’ perceptions of multiple trade unions in promoting professional development among teachers. The study objective specifically was; to examine teachers ‘perceptions of multiple trade unions in promoting professional development among Teachers. The study was in form of qualitative, it was a case study design involving ten public secondary school (A-J) in Dodoma city council. The population were Trade Unions’ Members, Trade Unions’ Leaders and Tanzania Registrar of Trade Unions. The sampling procedure used was purposive only, the sample size of 44 participants was employed. Two research instruments were used (focused group discussion and interview). Data was analyzed by using six stages of thematic analysis. The findings revealed teachers’ perceptions of multiple trade unions to promote professional development such as; reformation of the law of labour relation and education policy, collaboration between trade unions and the government in educational issues .Also to establish some programs such as trainings, workshops and seminars to promote teachers‘ professionalism. The government recommended to change the law of labour relation so as to reboots trade unions activities .Thus leaders of multiple trade unions were advised to re-examining the leadership and make restorations where necessary to make sure that unions’ activities are revived once again..